Potential of Noni Leaf Extract (Morinda citrifolia L.) As Aedes aegypti Mosquito Repellent - Demes Nurmayanti; Lailatul Fithriyah; Ngadino Ngadino; Irwan Sulistio; Slamet Wardoyo; Marlik Marlik; Mahawiraja Setiawan (Faculty of Public Health, Hasanuddin University, Makassar, 2024)
Dengue fever is transmitted every year by the Aedes aegypti mosquitoes in Indonesia. One way to prevent this is by using repellents, such as the noni leaf extract (Morinda citrifolia L.). The objective of this study was to analyze the potential of the noni fruit (Morinda citrifolia L.) leaf extract as a repellent against Aedes aegypti. The study employed a post-test research design with only a control group, using concentrations of 12.5%, 25%, and 37.5%, and 25 mosquitoes with 6 repetitions. The technique for data collection involved counting mosquitoes that perched on hands. The study was conducted from November 2022 to May 2023. Data analysis was performed using SPSS Anova One Away Post Hoc and the power protection formula. The research on Aedes aegypti mosquitoes that perched for 6 hours showed that the noni leaf extract concentration of 37.5% had an average of 2.5 tails perched. The concentration of the noni leaf extract is 37.5%, according to the Pesticide Committee standard (1995). The average protection power for 6 hours is 90.86%. The study also suggests investigating the side effects of use and the addition of an HPMC gelling agent. However, for concentrations of 12.5% and 25%, the protective power is less than 90%. This study shows that concentrations of 37.5% are effective for repelling Aedes aegypti mosquitoes. Further research can be conducted using old or yellowed leaves, as well as for repelling culex and Anopheles mosquitoes.